Validation of Database Designs on Ranganathan’s Normative Principles of Classification - Tapaswi, M. P. (Journal of Information and Knowledge, 1994)
The two database designs, based on the telescopic and partitioned approaches for universal use in the libraries have been validated on Ranganathan’s normative principles of classification. The design based on telescopic approach agrees well at the Idea Plane. Use of muemonic principles at Verbal and Notational Planes and also international standards like CCF for better compatibility are recommended.